Isoeugenol has a non-disruptive detergent-like mechanism of action - Hyldgaard, Morten; Mygind, Tina; Piotrowska, Roxana; Foss, Morten; Meyer, Rikke L. (Frontiers in Microbiology, 2015)
Isoeugenol is an essential oil constituent of nutmeg, clove, and cinnamon. Despite isoeugenol’s promising antimicrobial activity, no studies have yet investigated its mode of antibacterial action at the molecular level. The aim of this study is to clarify isoeugenol’s antibacterial mode of action using the Gram-negative and Gram-positive model organisms Escherichia coli and Listeria innocua, respectively. We determined the antimicrobial activity of isoeugenol against the model organisms, and examined how isoeugenol affects cell morphology, cell membrane permeabilization, and how isoeugenol interacts with phospholipid membranes using vesicle and supported lipid bilayer models. Isoeugenol demonstrated a bactericidal activity against E. coli and L. innocua that did not affect cell morphology, although the cell membrane was permeabilized. We hypothesized that the cell membrane was the primary site of action, and studied this interaction in further detail using purified membrane model systems. Isoeugenol’s permeabilization of calcein-encapsulated vesicles was concentration dependent, and isoeugenol’s interaction with giant unilamellar vesicles indicated increased membrane fluidity and a non-disruptive permeabilization mechanism. This contradicted membrane fluidity measurements on supported lipid bilayers, which indicated decreased membrane fluidity. However, further investigations demonstrated that the interaction between isoeugenol and bilayers was reversible, and caused membranes to display heterogeneous topography, an increased mass, and a higher degree of hydration. In conclusion, we propose that isoeugenol interacts with membranes in a reversible non-disruptive detergent-like manner, which causes membrane destabilization. Furthermore, we argue that isoeugenol increases membrane fluidity.